Analisis Laporan Keuanagan Dalam Menilai Kinerja Keuanaga Industry Barang Konsumsi Yang Terdaftar Di BEI (Studi Kasus PT Gudang Garam Tbk) - Reni U. Moidady; Elia Salamena; Nurhalisah Umaternate; Sastri Yusmita; Ignasius lakesjanan (Universitas 45 Surabaya, 2023)
Financial performance appraisal for companies is an important thing to do, this is used to measure and evaluate, so that a picture of the overall financial position is obtained. The method used to measure financial performance is one of the methods of financial statement analysis. The method of financial statement analysis involves several financial ratios, namely liquidity, solvency, activity, and profitability ratios. The purpose of this study is to determine the financial performance of PT Gudang Garam Tbk by using liquidity, solvency, activity, profitability ratios. The results of the discussion of the financial performance analysis show that the company PT Gudang Garam Tbk experienced several changes during the period 2018 to 2021. While there have been improvements in some financial ratios, such as Current Ratio and Gross Profit, there have also been some declining ratios, such as Receivables Turnover and ROE. This indicates that the company needs to further analyze and identify the causes of such fluctuations in order to take appropriate corrective measures so that financial performance can be improved.